A leitura jornalística na transição do papel para a tela : um modelo de análise psicolinguística - Elmi, Alexandre Claser (2020)
From a Psycholinguistics approach, this thesis proposes an interdisciplinary analysis model for journalistic reading, using concepts from the intervening variables of reading, as thought by Kenneth Goodman (1990). The goal is to develop a model that takes into account the notions of reading objectives, prior knowledge, type of text and reader's cognitive style. The construction may represent an alternative theoretical and methodological approach to understand the reading processing of journalistic texts, capable of collaborating to understand certain phenomena linked to the contemporary relationship between the journalistic reader and the journalistic text on digital platforms. Anchored mainly in the thinking of Roger Chartier (1999, 2002 and 2011) regarding the evolution of reading, it is admitted that contemporary reading manages the impact of digital support. The application of the model will be tested in a brief analysis of two journalistic products published in the monthly magazine piauí and in the digital journalism project UOL TAB, representatives of longform journalism in Brazil.